Management of Diffuse Large B-Cell Lymphoma as Post-Transplant Lymphoproliferative Disorder in a Kidney Transplant Recipient: A Case Report - Salem Alshemmari; Abdulaziz Hamadah; Samar Ousia; Rasha Abdel Tawab Hamed; Hany Zaky (Hematology Reports)
Background and Clinical Significance: Post-transplant lymphoproliferative disorder (PTLD) is a severe complication of solid organ transplantation, often associated with prolonged immunosuppression. Diffuse large B-cell lymphoma (DLBCL) is the most common subtype. Managing PTLD requires a balance between reducing immunosuppression and preventing graft rejection. Case Presentation: A 41-year-old female kidney transplant recipient developed PTLD eight years post-transplant, presenting with a right submandibular mass. Biopsy confirmed CD20-positive DLBCL. Initial treatment involved reducing immunosuppression and rituximab monotherapy, which failed to prevent disease progression. The patient underwent six cycles of R-CHOP chemotherapy, achieving complete metabolic remission. Relapse occurred twice, with disease progression in the cervical nodes and tonsils. Salvage therapies, including polatuzumab vedotin and rituximab, achieved remission. During a subsequent relapse, loncastuximab tesirine induced metabolic resolution. Compromised renal function limited treatment options and a second renal transplant was delayed, reducing the risk of PTLD recurrence. Conclusions: This case underscores the challenges of managing PTLD in transplant recipients, especially in relapsed/refractory cases. Single-agent rituximab was insufficient, but combination chemotherapy and novel agents like loncastuximab tesirine were effective. Balancing oncologic control and graft preservation remains critical. This case highlights the need for individualized approaches and novel therapies in managing PTLD while addressing the complexities of immunosuppression and organ preservation.